Effects of PLL and frequency measurements on LFC problem in multi-area HVDC interconnected systems. (October 2016) - Rakhshani, Elyas; Remon, Daniel; Rodriguez, Pedro
Highlights: The dynamic model of PLL (Phase Locked Loop) and frequency measurements in HVDC links is introduced and reflected in multi area AC/DC interconnected AGC systems. A complete state space mathematical model of multi area AC/DC interconnected LFC system with PLL and time delay is presented. time delays in LFC loop is added by introducing a Pade approximation. The dynamic effects of PLL with different parameters are analyzed for different test system (two-area and four area models). Eigenvalue and Sensitivity analysis is performed to show the marginal values of delay for stability. The proposed approach will be very useful and essential for future research in LFC adding the converter based models or HVDC links. It could be easily implemented for any type of interconnected power systems with different size and characteristics. Abstract: Recent advancements in power electronics have made HVDC links and renewable based generation more popular in power systems application with better grid support functionalities like frequency control and inertia emulation tasks. Conventional operation and control strategies are undergoing of different changes and all the infrastructure of future modern power system should efficiently support the delivery of ancillary services in complex scenarios of AC/DC multi-area interconnected system. The AGC system of tomorrow must be able to handle complex interactions between control areas with HVDC links and distributed generation equipment. In such scenario, the effects of wide-area interconnections, PLL (Phase Locked Loop) and frequency measurements cannot be ignored. The dynamics effects of PLL and frequency measurements are very important for HVDC operation. For obtaining an acceptable performance of AC/DC system, the dynamic models of PLL and measurements need to be taken into account. This paper focused on the effects of PLL and frequency measurements in frequency supports of HVDC interconnected system. A novel approach for analyzing the dynamic effects of HVDC links considering PLL effects during coordination with AC system is presented and discussed. The effects of PLL are considered by introducing a second-order function. A Pade approximation method is also introduced for adding the effects of communication delays on AGC operation and the state space models are presented. The proposed model is analyzed for different multi-area test systems which contains parallel AC/DC transmission links.